Super Manny stands up! - DiPucchio, Kelly (Atheneum Books for Young Readers, an imprint of Simon & Schuster Children's Publishing Division, 2017)
"The story of a brave little raccoon named Manny, whose superhero games at home give him unexpected strength at school when he puts on his invisible cape to stand up to a bully"--